Strengthening the Understanding of Religious Moderation among Students at Pondok Pesantren Daarul Falahiyyah, Cisoka District, Tangerang Regency - Ahmad Khunaepi; Dul Jalil (International Research and Development for Human Beings (IRDH), 2025)
This research activity aims to strengthen the understanding of religious moderation among students at the Daarul Falahiyyah Islamic Boarding School in Cisoka District, Tangerang Regency. Religious moderation is crucial in the context of Indonesia's diverse religious life, so that the values of tolerance, justice, and balance can be maintained and practiced. Islamic boarding schools, as traditional religious educational institutions, have a strategic role in instilling these values in students. This activity was carried out in the form of a seminar and interactive discussion involving 60 students as active participants. The seminar was held in August 2025 and focused on strengthening the concepts of religious moderation, such as tawassuth (middle-mannerism), tasamuh (tolerance), i'tidal (justice), and shura (deliberation). The implementation method prioritized a participatory approach so that students could engage in dialogue and think critically about the socio-religious realities they face. The results of the activity showed an increase in students' understanding of the importance of being moderate in religious and social life. This community service is expected to make a tangible contribution to developing an inclusive, tolerant, and patriotic young generation of Muslims. By actively involving Islamic boarding schools (pesantren), this activity also serves as an initial step toward mainstreaming religious moderation in grassroots Islamic educational institutions.